Cutaneous-Ocular Manifestations in Systemic Inflammatory Diseases: Clinical Patterns, Early Recognition, and Multidisciplinary Management - Ana Patricia Torres Barrios; Sandra Carolina Méndez Sosa; Luis Felipe Espinal Pérez; Cruz Vargas Katherine Gisela; José Arnulfo Pérez Carrillo; Madelayne Lourdes Mejía Concha; Katherine Guissela Garza Córdova; Diego Alejandro Rojas López (IECCMEXICO, 2026)
Systemic inflammatory diseases may simultaneously affect the skin and ocular structures, generating clinical patterns that can contribute to earlier recognition of underlying immune-mediated disorders. This review analyzed the relationship between cutaneous and ocular manifestations in systemic lupus erythematosus, Sjögren’s syndrome, Behçet’s syndrome, sarcoidosis, dermatomyositis, granulomatosis with polyangiitis, systemic sclerosis, and psoriasis, with emphasis on early diagnosis and comprehensive management. An integrative literature review was conducted using the Scientific Method as the methodological framework, prioritizing peer-reviewed publications, systematic reviews, clinical reviews, diagnostic criteria, and international recommendations. The evidence was organized according to pathophysiological mechanisms, dermatological manifestations, ocular findings, diagnostic warning signs, complementary studies, and therapeutic strategies. The analysis identified recurrent cutaneous patterns including papular, plaque, nodular, erythematous, photosensitive, vasculitic, purpuric, mucosal, telangiectatic, periungual, and xerotic manifestations. Ocular involvement included dry eye disease, uveitis, retinal vascular and microvascular abnormalities, scleritis, episcleritis, keratitis, conjunctival and lacrimal involvement, optic neuropathy, and orbital inflammation. Systemic lupus erythematosus showed the broadest combined spectrum of manifestations, whereas Behçet’s syndrome, granulomatosis with polyangiitis, and sarcoidosis were particularly relevant because of potentially sight-threatening inflammatory involvement. Systemic clinical assessment and multidisciplinary follow-up were consistently identified as central components of management, accompanied by targeted laboratory testing, specialized ophthalmological evaluation, histopathology when appropriate, corticosteroids, conventional immunosuppressive agents, and biologic or targeted therapies according to disease severity. The findings indicate that the diagnostic value of cutaneous and ocular manifestations depends primarily on their combination, chronology, severity, and systemic context rather than on isolated findings. Integrating dermatological and ophthalmological assessment with systemic evaluation may facilitate earlier diagnosis, improve clinical stratification, guide timely treatment, and reduce the risk of irreversible visual and systemic complications.